CLINICAL AND CT SCAN DIFFERENCES BETWEEN PATIENTS WITH AND WITHOUT PARALYSIS SYMPTOMS IN CHRONIC SUBDURAL HEMATOMA - Đỗ Khắc Hậu,; Lê ngọc, Vũ; Hoang The Anh,; Nguyễn Thành , Bắc; Nguyễn Xuân, Phương (Tạp chí Y học Quân sự, 2025)
Objective: To investigate the clinical and CT imagining difference in patients with chronic subdural hematoma who present with or without hemiparesis symptoms. Subjects and methods: A restrospective and prospective, comparison study was conducted on 142 patients with chronic subdural hematoma who underwent surgical treatment at Military Hospital 103 and Central Military Hospital 108 from January, 2022 to January, 2024. Results: The average age of patients was 67.2 ± 11.5 years. Most patients were male (83.1%) and 64.8% had hemiparesis symptoms. Clinically, in the group without hemiparesis, the rate of headache was 98.0%, there were no cases of cognitive disorder (0%), the average age was 62.3 ± 11,9 years, and the average Glasgow Coma Scale score was 15 ± 1 points, statistically different compared to the group with hemiparesis (with rates of 86.9%; 13.0%; 69.8 ± 10.5 years; and 14 ± 1 points respective), with p < 0.05. On CT imaging, hematoma thickness, midline shift, and injury location in patients without hemiparesis symptoms were statistically different compared to those with hemiparesis, with p < 0.05.